Cross-quality impacts of NCAA Division I baseball and softball - Beaudin, L. (Journal of Sports Economics, 2024)
Fifty years after Title IX, inequalities still exist between men's and women's sports. Most sport studies still fail to examine women's sports. This study explores the cross-quality impacts of Division I baseball and softball teams. The softball team win percentage is positively related to softball and baseball game attendance. However, models produce mixed results for the impact of the quality of the baseball team. Therefore, improving the strength of the softball team could increase softball and baseball game attendance, while improving the strength of the baseball team might only increase attendance at baseball games.